Trade, manufacturing and the economics of Europe's emergencies - Giuseppe Bertola (EconPol Forum, 2024)
Decarbonization and security are worthy goals, but it would be a mistake to think that protection and subsidization of domestic manufacturing reduce their cost. Trade restrictions decrease economic efficiency. Creating manufacturing jobs may sound like a benefit, but in advanced countries it increases costs. Subsidy-based policies are prone to capture by special interests and need to be funded by tax or debt, which introduce distortions of their own and reduce economic efficiency. In theory and in history, wars and climate change are bad, and worse when sanctions and environmental policies cut off beneficial trade opportunities. Circumstances may call for building costly walls around a fortress Europe, but strengthening markets, trust, and policies within the EU should have the highest priority.
Keywords: 330